Analisis Implementasi Akad Murabahah di KSPPS BMT Amanah Ummah Berdasarkan Fatwa DSN dan KHES - Istiana, Muflihah; Yahya, Ismail (Jurnal Hukum Ekonomi Syariah, 2025)
This study discusses the implementation of the Murabahah contract in the financing process and the resolution of issues such as non-performing financing and defaults at KSPPS BMT Amanah Ummah. This research employs a qualitative method with a descriptive approach. Data were obtained from primary sources such as observations and interviews, as well as secondary sources including BMT AUM archives, literature studies, and information from social media. Data analysis was conducted using observation and documentation techniques. The research findings indicate that the implementation of the Murabahah contract at BMT Amanah Ummah complies with the provisions of the Sharia Economic Law Compilation (KHES) articles 116–133 and DSN MUI Fatwa No.04/DSN-MUI/IV/2000 on Murabahah, particularly in aspects of financing, installment payments, the resolution of non-performing loans, and the provision of collateral goods. This implementation reflects BMT Amanah Ummah’s commitment to upholding sharia principles in an orderly and professional manner. Furthermore, the resolution mechanism for problematic financing is carried out through deliberative approaches and refers to Islamic economic law provisions. This study also emphasizes the importance of DSN MUI fatwas and KHES as operational guidelines for Islamic financial institutions. The findings are expected to serve as a practical reference for other Islamic cooperatives in managing Murabahah contracts. Thus, the integration of sharia regulations in financial practices can be increasingly optimal and sustainable. Keywords: Murabahah Contract, KSPPS, BMT Amanah Ummah, DSN MUI Fatwa, KHES (Compilation of Sharia Economic Law)